EFFECT OF SPRAYING ORGANIC EMULSION (APPETIZER) AND NANO NPK WITH UREA ON SOME GROWTH CHARACTERISTICS OF THREE SYNTHETIC CULTIVARS OF MAIZE: EFFECT OF SPRAYING ORGANIC EMULSION (APPETIZER) AND NANO NPK WITH UREA ON SOME GROWTH CHARACTERISTICS OF THREE SYNTHETIC CULTIVARS OF MAIZE (Iraqi Journal of Market Research and Consumer Protection, 2022)
A field experiment was carried out at the research station of the College of Agriculture - Wasit University / Kut, during the fall season 2021 in soil with texture (sandy mixture) using the RCBD design in the arrangement of splintered plates and with three replications, to study the effect of spraying different combinations of organic emulsion (Appetizer) and NPK nano fertilizer with urea fertilizer on the growth of synthetic cultivars of yellow corn. The main panels included three synthetic varieties of yellow corn (Fajr1, Sumer and Baghdad3), which symbolized by (V1,V2,V3) in sequence, while the secondary panels included five fertilization treatments in which mineral fertilizer (urea) was used 46% nitrogen with the full recommendation (300 kg/ha-1) (control treatment) symbolized by T1 and (adding urea according to the recommendation with the addition of the organic emulsion (Appetizer) in two batches before flowering and full flowering) and symbolized by T2 and (adding urea according to the recommendation with nano-NPK in two batches before flowering and full flowering) and symbolized by T3 and (reduction of the recommendation treatment in the first and second batches with the addition of the organic emulsion (Appetizer) in two batches before flowering and full flowering) and symbolized by T4 and (reduction of the recommendation treatment in the first and second batches with the addition of nano-NPK in two batches before flowering and full flowering) It is symbolized by T5. The results showed that there were significant differences between the different fertilization treatments, as the T5 nano fertilization treatment achieved the highest average in most of the growth and quality indicators, It gave the highest average number of days from planting up to 75% of male flowering amounted to 68.00 days and the highest average number of days from planting to 75% of female flowering amounted to 73.44 days and the highest plant height (172.96 cm) and ear height (70.01 cm), the number of leaves per plant (15.23) and the content of The chlorophyll of the leaf under the ear (60.09). The results also showed that the Baghdad3 variety excelled in most of the growth indicators and gave the highest average number of days from planting up to 75% of male flowering amounting to 66.07 days and the highest average number of days from planting up to 75% of female flowering amounted to 72.00 days and the highest plant height (170.04 cm) and ear height (67.11 cm), the number of leaves per plant (14.26), the chlorophyll content of the leaf under the ear (55.49). The interaction between fertilization treatments and cultivars was not significant for most of the growth characteristics.